ALIH KODE DAN CAMPUR KODE PADA PEMERAN UTAMA ZAINUDDIN DALAM FILM TENGGELAMNYA KAPAL VAN DER WIJCK - Fiddienika, Arief; Awaliyah, Nur Iffa; Akuba, Annisa Salsabilah (Universitas Negeri Makassar, 2024)
The purpose of this research is to describe the form and factors that cause code switching and code mixing in the movie